Caregiver Knowledge and Functional Status in Preventing Pressure Ulcers among Stroke Patients: A Cross-Sectional Study - Damanik, chrisyen; Pratama, Salwa Setya Anggun (Journal of Applied Nursing and Health, 2025)
Background: Stroke is a leading cause of death and disability, often reducing patients' quality of life and increasing caregiver burden. Immobility after stroke raises the risk of pressure ulcers, worsening outcomes, and prolonging hospital stays. Caregivers are crucial in prevention, as their knowledge and functional ability affect care effectiveness. However, few studies have explored the direct link between caregiver knowledge and functional status in pressure ulcer prevention, particularly in home or community settings. This study aims to examine that relationship. Methods: This cross-sectional study (June–July 2025) in Indonesia involved 38 primary caregivers of stroke patients, selected via consecutive sampling. Eligible caregivers were ≥18 years old, had ≥1 month of caregiving experience, and consented; professional caregivers and those caring for acute-phase patients were excluded. Data were collected using bilingual questionnaires on caregiver knowledge (15 items, α = 0.739) and functional status (18 items, α = 0.878). Descriptive statistics summarized participant characteristics, and Pearson’s correlation analyzed the relationship between knowledge and functional status. Results: Most caregivers were aged 46–55 (42.1%), female (76.3%), educated to junior/high school level (71.1%), and predominantly housewives (47.4%). A majority (76.3%) had no prior caregiving experience. The mean knowledge and functional status scores were 10.58 ± 1.605 and 61.95 ± 4.550, respectively. Pearson’s correlation revealed a strong, significant positive relationship between caregiver knowledge and functional status (r = 0.634; p < 0.001), suggesting that greater understanding of pressure ulcer prevention is associated with improved caregiving performance in stroke care. Conclusion: Caregivers’ knowledge and functional status directly affect their effectiveness in stroke care. Better-informed caregivers more successfully prevent pressure ulcers, emphasizing the need for structured training programs that build skills and confidence, improve patient outcomes, and reduce complications.